Prevalence of the second mesiobuccal canal of maxillary molars in the South American population: a systematic review and meta-analysis of CBCT studies - Kevin José Poclin-Quispe; Heber Isac Arbildo-Vega; Fray L. Becerra-Suarez; Gabriel Guerra-Gonzales; David Yeret Rodríguez-Salazar; Franz Tito Coronel-Zubiate (Frontiers in Dental Medicine, 2026)
Background The objective of this systematic review and meta-analysis was to determine the prevalence of the second mesiobuccal (MB2) canal in permanent maxillary molars within the South American population, evaluated exclusively through cone-beam computed tomography (CBCT). Methods Following the PRISMA guidelines, an electronic search was conducted across PubMed, Scopus, Web of Science, Embase, SciELO, LILACS, and gray literature until May 2026. Observational studies published from 1990 onwards were included. A meta-analysis of proportions was executed using a random-effects model. The risk of bias was assessed with the JBI tool, and the certainty of evidence using the GRADE framework. Results A total of 23 observational studies were included. The pooled overall prevalence of the MB2 canal was 59% (95% CI: 53%–66%). In the tooth-specific analysis, prevalence reached 66% in first molars and 41% in second molars. Significant sexual dimorphism was evident in second molars, where males presented a 35% higher probability of possessing the canal (OR = 1.35). The GRADE analysis indicated a High certainty for the overall and first molar prevalences, and Moderate for second molars. Conclusions The MB2 canal is a highly prevalent anatomical variation in South America, constituting the anatomical norm in first molars. The clinical use of CBCT is crucial for its diagnostic prediction and successful management. Systematic Review Registration DOI: 10.17605/OSF.IO/KRG4Z .